The genetic diversity of Icelandic populations of two barley leaf pathogens, Rhynchosporium commune and Pyrenophora teres - Stefansson, Tryggvi S.; Serenius, Marjo; Hallsson, Jon Hallsteinn (European Journal of Plant Pathology, 2012)
v 2012 ok